Conspicuous consumption, inequality and debt: The nature of consumption-driven profit-led regimes - Jakob Kapeller; Bernhard Schütz (Johannes Kepler University of Linz, Department of Economics, 2012)
This paper extends the theoretical concept of wage-led and profit-led demand regimes, first introduced by Amit Bhaduri and Steven Marglin in the early 1990s, by incorporating relative consumption concerns. Specifically, it integrates the Veblenian concept of conspicuous consumption into a typical Bhaduri-Marglin model by assuming that relative consumption concerns matter primarily within the working class. If in such a framework the profit share increases and the corresponding decrease in workers' income is distributed unevenly, efforts to keep up with the Joneses may increase consumption and, hence, lead to a consumption- driven profit-led regime. The model's empirical relevance is illustrated with respect to the pre-crisis developments as observed in the U.S.
Keywords: B52; D11; E12; E20; 330